Experiences of having lived with Broca's aphasia: a scoping review - Ana Frade; Vanda Marques Pinto; Luísa D'Espiney (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2023)
Introduction: Broca's aphasia, a non-fluent aphasia, is a frustrating condition with extensive psychological, familial, and social impact. The reports of people who have already recovered or can express themselves are essential to increasing knowledge about the experience of living with Broca's aphasia. A-FROM is a framework designed to organize thinking about the impact of living with aphasia and includes four key domains: Communication and language environment; Language and related impairments; Personal identity, attitudes and feelings, and Participation in life situations. Nursing intervention is central to optimizing recovery and positively influencing the experience of successfully living with this clinical condition. Objective: To map scientific evidence about the experience of people who lived through a period of Broca's aphasia. Methods: A Scoping Review was performed following the Joanna Briggs Institute methodology. The review was based on the research question, "How does the person report the experience of having lived through a period of Broca's aphasia?", formulated according to the PCC strategy. The search was carried out in MEDLINE®, CINAHL®, Psychology and Behavioral Sciences Collection, and Scopus electronic databases in November 2022. Articles were selected based on the eligibility criteria. The review followed the PRISMA-ScR EQUATOR checklist. Results: Seventeen articles published between 1961 and 2022 were included. Data obtained were grouped according to the key domains of the A-FROM tool. Information related to Personal identity, attitudes and feelings, and Participation in life situations were the most cited, followed by Language and related impairments and Communication and language environment. Conclusion: It was identified that health professionals, therapeutic interventions, spirituality, hope, context, interactions, and psychosocial factors influence the experience of Broca's aphasia. It is essential to continue investigating how people report the experience of having lived through a period of Broca's aphasia to improve the quality of care and people's quality of life.